Report of the Achimota Conference - Achie-Menson, C.W.T (Government Printing Department, 1956)
The Conference to consider the Report of the Constitutional Adviser, Sir Frederick Bourne, K.C.S.l.C.I.E., and matters arising therefrom was convened by the Prime Minister of the Gold Coast, the Honourable Dr. Kwame Nkrumah, M.L.A., LL.D., who later agreed that the terms of reference of the Conference should be enlarged to include matters raised in correspondence by the Asanteman Council and by the National Liberation Movement and its allies.
Folio Collection
Keywords: Conference; Constitutional Adviser